Surgery or in vitro fertilization: The simplicity of this question belies its complexity. (6th December 2017) - Yazdani, Anusch
Abstract : Unlike surgery, assisted reproduction, particularly in vitro fertilisation (IVF), requires a low skill base, is largely practitioner independent, is highly effective, quality controlled, reproducible and consistent in the management of endometriosis‐associated infertility. Ultimately, however, the decision to proceed to IVF or surgery is dependent on the woman, her reproductive expectations, her specific disease pattern, her support and family network and the resources available in a given health care setting.